2012
DOI: 10.1063/1.4754273
|View full text |Cite
|
Sign up to set email alerts
|

Competitive fragmentation pathways of acetic acid dimer explored by synchrotron VUV photoionization mass spectrometry and electronic structure calculations

Abstract: In present study, photoionization and dissociation of acetic acid dimers have been studied with the synchrotron vacuum ultraviolet photoionization mass spectrometry and theoretical calculations. Besides the intense signal corresponding to protonated cluster ions (CH(3)COOH)(n)·H(+), the feature related to the fragment ions (CH(3)COOH)H(+)·COO (105 amu) via β-carbon-carbon bond cleavage is observed. By scanning photoionization efficiency spectra, appearance energies of the fragments (CH(3)COOH)·H(+) and (CH(3)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…Reference spectra of acetic acid show the appearance at m/z = 61 assigned to protonated acetic acid (CH 3 COOH)H + . This mass peak has also been observed in VUV photoionisation studies of acetic acid clusters (Guan et al 2012). An additional intensity decrease is observed at m/z = 45 and 46, which can be explained by the desorption of the remaining ethanol.…”
Section: (125-150 K): Identification Of Ch 3 Oh Ch 3 Ch 2 Oh and Hmentioning
confidence: 73%
“…Reference spectra of acetic acid show the appearance at m/z = 61 assigned to protonated acetic acid (CH 3 COOH)H + . This mass peak has also been observed in VUV photoionisation studies of acetic acid clusters (Guan et al 2012). An additional intensity decrease is observed at m/z = 45 and 46, which can be explained by the desorption of the remaining ethanol.…”
Section: (125-150 K): Identification Of Ch 3 Oh Ch 3 Ch 2 Oh and Hmentioning
confidence: 73%
“…from two fragments of the dimer: (CH 3 COOH)•H + (m/z=61) and (CH 3 COOH)•COOH + (m/z=105), as will be demonstrated. Fragments of trimers were not detected either because of the relatively low conversion of carbon dioxide-methane to acetic acid or because the energy used to photoionize the subliming molecules in our experiments is insufficient to produce trimer fragments such as (CH 3 COOH)•CH 3 CO + (m/z=103), which has an appearance energy of 12.41 eV (Guan et al 2012).…”
Section: Pi-retof-ms-acetic Acidmentioning
confidence: 91%
“…In principle, since the IE of all C 2 H 4 O 2 isomers is below the photoionization energy of 10.84 eV used in the present experiments, the specific assignment of the signal at m/z= 60 to one species in particular would not be possible. However, laboratory studies have revealed that gas-phase acetic acid (CH 3 COOH) forms a strongly bound dimer (CH 3 COOH) 2 involving two hydrogen bonds (Forysinski et al 2011;Guan et al 2012), while the hydrogen bonding in the trimer (CH 3 COOH) 3 was shown to be less favorable. Using supersonic beams of acetic acid monomers, dimers, and trimers, coupled to tunable vacuum ultraviolet light, to detect and count the resulting ions, Guan et al (2012), Hu et al (2006), and Zielke et al (2009) revealed that upon soft photoionization ionized acetic acid dimers and trimers undergo reaction and fragment in a pattern characterized by signal from acetic acid (CH 3 COOH + ) (m/z= 60), by protonated clusters (…”
Section: Pi-retof-ms-acetic Acidmentioning
confidence: 99%
See 2 more Smart Citations